Eriophyoid mites from Northeast China (Acari: Eriophyoidea) - Xue, Xiao-Feng; Guo, Jing-Feng; Hong, Xiao-Yue (Zootaxa, 2013)
We describe and illustrate herein one new genus and eighteen new eriophyoid mite species (Acari: Eriophyoidea) collected in northeast China. They are: Shevtchenkella huzhongiensis sp. nov. on Ulmus davidiana Planch. var. japonica (Sarg. ex Rehder) Nakai (Ulmaceae), Shevtchenkella jingboicus sp. nov. on Acer sp. (Aceraceae), Calepitrimerus flexuosus sp. nov. on Spiraea flexuosa Fisch. ex Cambess. (Rosaceae), Calepitrimerus maximowiczii sp. nov. on Crataegus maximowiczii Schneid. (Rosaceae), Calepitrimerus pilosus sp. nov. on Agrimonia pilosa Ledeb. (Rosaceae), Calepitrimerus yichunensis sp. nov. on Sorbaria sorbifolia (L.) A.Br. (Rosaceae), Cupacarus oxyphyllus sp. nov. on Euonymus oxyphyllus Miq. (Celastraceae), Epitrimerus sambucus sp. nov. on Sambucus williamsii Hance (Caprifoliaceae), Epitrimerus wuyingensis sp. nov. on Acer sp. (Aceraceae), Longisolenidionus amurensis gen. nov & sp. nov. on Tilia amurensis Rupr. (Tiliaceae), Phyllocoptes jiagedaqiensis sp. nov. on Cunninghamia sp. (Taxodiaceae), Aculops huzhongensis sp. nov. on Salix sp. (Salicaceae), Aculus huzhongsalixus sp. nov. on Salix sp. (Salicaceae), Tetra angelica sp. nov. on Angelica sp. (Apiaceae), Tetra jiagedaqia sp. nov. on Lespedeza sp. (Fabaceae), Vittacus mandshurica sp. nov. on Corylus sieboldiana Blume var. mandshurica (Maxim.) C. K. Schneid. (Betulaceae), Vittacus cannabus sp. nov. on Cannabis sativa L. (Moraceae), and Peralox dentatis sp. nov. on Ulmus sp. (Ulmaceae). Two species formerly assigned to Rhyncaphytoptus, R. abiesis (Xue, Song & Hong, 2006) and R. fabris (Xue, Song & Hong, 2006) were reassigned to Nalepella, based on the presence of seta vi on the apical shield, and other characteristics of Nalepella. One species formerly assigned to Rhyncaphytoptus, R. fargesis (Xue, Song & Hong, 2006) was reassigned to Pentaporca, based on the presence of seta vi on the apical shield, opisthosoma with five ridges and other characteristics of Pentaporca. At the same time, four new eriophyoid mite records from China are provided, Acaphyllisa distasa (Keifer, 1961) rec. nov. on Betula costata Trautv. (Betulaceae), Shevtchenkella ulmi (Farkas, 1960) rec. nov. on Ulmus sp. (Ulmaceae), Calepitrimerus cariniferus Keifer, 1938, rec. nov. on Artemisia argyi H. Lev. & Vaniot (Asteraceae), Aculodes dubius (Nalepa, 1891) species complex, rec. nov. on Roegneria sp. (Poaceae). With this publication, the number of eriophyoid mite species in the region reaches 101. A list of these eriophyoid mites is provided.